Bond-slip behaviour between GFRP/steel bars and seawater concrete after exposure to environmental conditions. (1st October 2022) - Kazemi, Hamidreza; Yekrangnia, Mohammad; Shakiba, Milad; Bazli, Milad; Vatani Oskouei, Asghar
Highlights: Bond performance between GFRP bars and seawater concrete. Effect of moisture, seawater, and wet-dry cycles on bond performance of GFRP reinforced concrete. Comparing the bond behaviour between GFRP and steel reinforced seawater concrete. Abstract: Corrosion resistant FRP reinforced seawater concrete structures are attractive alternatives to conventional steel reinforced normal concrete structures. In this experimental study, the bond-slip durability of glass fibre reinforced polymer (GFRP) and steel bars embedded in seawater concrete after exposure to environmental conditions has been studied. Specimens with bars embedded in normal concrete were also tested for comparison. In total, 48 cubic specimens were constructed, conditioned, and tested under a direct pull-out test. Four environmental conditions, including the ambient weather, immersion in tap water, immersion in seawater, and seawater wet-dry cycles were used in this study. The results showed the maximum bond strength reductions of about 6 % and 10 % of steel reinforced normal concrete after 250 days of exposure to seawater and seawater wet-dry cycles, respectively compared to the specimens conditioned at ambient weather. The corresponding strengths reductions were 8 % and 13 % for steel reinforced seawater concrete. However, due to the compressive strength increment of specimens exposed to tap water immersion (better curing than ambient weather), a slight bond strength increments up to 4 % was found in both normal and seawater concretes reinforced with steel bars. With respect to GFRP reinforced concrete samples, similar to steel bars, bond strength increments of about 5 % and 13 % after 250 days of immersion in tap water were obtained for normal and seawater concretes, respectively. However, small reductions of 2 % and 3 % were observed in GFRP reinforced normal concretes after exposure to seawater and wet-dry cycles, respectively. The corresponding values were 20 % and 8 % for GFRP reinforced seawater concrete specimens.